Short Stories for English Courses - Mikels, Rosa Mary Redding, 1862- (Salt Lake City, UT : Project Gutenberg, 2004)
"Short Stories for English Courses" by Rosa Mary Redding Mikels is a collection of short stories edited for educational use, likely compiled in the late 19th century or early 20th century. The collection is designed to provide high school students with engaging and diverse reading material that emphasizes the qualities of short fiction, offering stories from a range of notable authors aimed at enhancing students' understanding and appreciation of this literary form. The opening portion introduces the purpose and structure of the anthology, addressing the need for contemporary literature in the classroom to captivate young readers. It discusses the significance of the short story as an art form that reflects modern life and is accompanied by practical advice on how to utilize the book for both enjoyment and educational development. The editor expresses the hope that the selected stories will assist students in distinguishing between well-crafted narratives and lesser works, ultimately fostering a deeper appreciation for literature as they progress through adolescence. (This is an automatically generated summary.)
Preface -- Introduction: Requirements of the short story. How this book may be used -- The first Christmas-tree / Henry Van Dyke -- A French tar-baby / J.C. Harris -- Sonny's christenin' / Ruth M. Stuart -- Christmas night with Satan / John Fox, Jr. -- A nest-egg / J.W. Riley -- Wee Willie Winkie / Rudyard Kipling -- The gold bug / E.A. Poe -- The ransom of Red Chief / O. Henry -- The freshman full-back / R.D. Pane -- Gallegher / R.H. Davis -- The jumping frog / Mark Twain -- The lady or the tiger? / F.R. Stockton -- The outcasts of Poker Flat / F.B. Harte -- The revolt of mother / Mary E.W. Freeman -- Marse Chan / T.N. Page -- "Posson Jone'" / G.W. Cable -- Our aromatic uncle / H.C. Bunner -- Quality / John Galsworthy -- The triumph of night / Edith Wharton -- A messenger / Mary R.S. Andrews -- Markheim / R.L. Stevenson.
Release date is 2004-04-01
Produced by Robert Rowe, Charles Franks and the Online Distributed Proofreading Team
Keywords: Short stories, American